Algorithmic-knowledge-based adaptive coordination in transmission protection. - Orduna, E.
Changes in power system operating conditions can affect both the reach point of distance relays and the coordination of distance and overcurrent relays. To improve the performance of the protection system, an adaptive scheme of relay settings is proposed. That is possible since the protection relays became digital . This paper describes a system for online adaptive setting and coordination of protection relays in meshed networks where the backup protection is achieved in remote form. After changes in the state of the network, an expert system (ES) performs the detection and proposes the correction of erroneous settings of protection zones and miscoordinations between relays at different stations; through an algorithm based on a fast determination of a nonminimal set of "break-points" (BPs) relays , new time characteristics for the coordination are found. The results of the application of the developed system to a test network of 34 nodes, 55 branches, and 110 relays are shown.
Keywords: Algorithmic-knowledge-based adaptive coordination; Backup protection; Break-points.; Distance relays coordination; Erroneous settings correction; Expert system; Meshed networks; Miscoordinations; Online adaptive setting; Overcurrent relays coordination; Power system operating conditions; Time characteristics; Transmission protection